2012
DOI: 10.1177/1934578x1200701230
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antimicrobial and Antioxidant Properties of the Volatile Oil and Methanol Extract of Xenophyllum Poposum

Abstract: The essential oil and methanol extract of northwestern Argentina medicinal plant Xenophyllum poposum, collected in Catamarca province, were investigated. GC and GC-MS analyses of the essential oil identified 56 compounds accounting for 92.9%. The main components of the oil were -cadinene (16.5%), 6-hydroxytremetone (14.7%), epi--cadinol (12.0%), -cadinol (8.8%), -cadinene (7.5%), 1-epi-cubenol (4.2%) and -muurolene (3.0%). The essential oil exhibited antibacterial activities against five pathogenic strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 18 publications
0
20
0
1
Order By: Relevance
“…As no study investigated the antifungal effect of this latter compound, the activity shown by the use of H. pandurifolim EO might owing to the synergic effect of the whole constituents, even those present in a lesser amount. In fact, several compounds associated with several EOs demonstrating good antifungal activities are reported in the literature such as β -pinene, spathulenol, δ -cadinene, and epi- α -muurolol [ 37 , 38 , 39 , 40 ]. The sensitivity of fungi rather than bacteria was registered again using the H. cooperi EO.…”
Section: Resultsmentioning
confidence: 99%
“…As no study investigated the antifungal effect of this latter compound, the activity shown by the use of H. pandurifolim EO might owing to the synergic effect of the whole constituents, even those present in a lesser amount. In fact, several compounds associated with several EOs demonstrating good antifungal activities are reported in the literature such as β -pinene, spathulenol, δ -cadinene, and epi- α -muurolol [ 37 , 38 , 39 , 40 ]. The sensitivity of fungi rather than bacteria was registered again using the H. cooperi EO.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical composition was checked, revealing that H. pandurifolium was rich in viridiflor and contains beta pinene, spathulenol, delta cadinene, and epi-alfa-muurolol [ 123 , 124 , 125 , 126 ], which probably develop a synergistic action. The effectiveness of H. cooperi would be due to the presence of a good amount of terpinen-4-ol [ 127 ] and himachalol [ 128 ], while the richness in tujone of H. edwardsii could explain its ability in inhibiting dermatophytes [ 55 ].…”
Section: Fungal Infectionsmentioning
confidence: 99%
“…In the same way as EOs from S. odoratissima, γcadinene was one of the major constituents of the oil. In addition, the compound γ-cadinene was one of the major constituents of EOs from Xenophyllum poposum, which also exhibited pronounced antibacterial activity against two strains of Staphylococcus aureus (González et al, 2012). It is usually assumed that non-polar compounds diffuse easily across cell membranes and kill microorganisms by affecting bacterial metabolic pathways or organelles.…”
Section: Resultsmentioning
confidence: 99%